A STEM CELL OVERVIEW – FROM EVOLVING HEMOBIOLOGICAL CONCEPTS TO (AUTO)GRAFTING IN CLINICAL PRACTICE - Balint, Bela; Pavlovic, Mirjana; Markovic, Olivera; Borovic, Sasa; Todorovic, Milena (Srpski medicinski časopis Lekarske komore, 2022)
Conventional hematopoietic stem cell transplantation is a well-known treatment method for numerous acquired and congenital hematopoietic disorders, disorders of the immune system, as well as certain metabolic disorders. Stem cells (SCs) can be defined as cells capable of self-renewal with a high proliferative capacity and the potential to differentiate into functionally competent mature cells. Stem cells can be divided into embryonic SCs (ESCs) and tissue-specific or adult SCs – such as bone marrow (BM) stem cells, peripheralblood (PB) stem cells, and SCs derived from umbilical cord blood (UCB), as well as other non-hematopoietic or somatic SCs. SCs in adults are characteristically considered to be restricted in their regenerative and differentiative potential, while embryonic stem cells are ‘true’ totipotent/pluripotent cells, due to their ability to develop into endoderm, ectoderm, or mesoderm – all three embryonic tissue types in the human body. They are the most promising, but also the most controversial type of potentially transplantable SCs.Immature hematopoietic SCs have the potential of differentiating, not only into all blood cells, but also into some somatic cell types (SC plasticity). In different clinical settings, the transplantation of immature stem cells leads to the repopulation of recipient bone marrow, with subsequent complete, stable, and long-term reconstitution of hematopoiesis. Given that immature stem cells are also capable of homing to different tissues, autologous stem cell implantation into a damaged and/or ischemic area induces their colonizing andconsecutive transdifferentiating into cell lineages of the host organ, including neovascularization. Thus, they are clinically applicable in the field of regenerative medicine for the treatment of myocardial, brain, vascular, liver, pancreatic, and other tissue damage. The purpose of this overview is to recapitulate the key developments in the rapidly evolving area of stem cell research, as well as to review the use of SCs in conventional transplantations and in regenerative medicine. Additionally, a brief critical evaluation of our own stem cell research will be summarized.
Keywords: stem cells; SC plasticity; transplantation; regenerative medicine